Pengaruh Pengetahuan Ibu Tentang Gizi Dan Pola Pemberian Makan Terhadap Kejadian Gizi Kurang Pada Balita Di Wilayah Kerja Puskesmas Gajahan Surakarta - Damayanti, Rina, Endang Zulaicha Susilaningsih, S.Kp., M.Kep (2017)
Nutrition deficiency became one of the main nutritional problems in Indonesia. The prevalence of nutrition deficiency on toddlers based on index weight according to age (w/U) in Indonesia gives an fluctuating so the Government emphasizes Healthy Indonesia Program with one of the principal targets of the medium-term National development plan 2015 until the year 2019, namely increasing the nutritional health status of mothers and children. This research aims to know the influence of the mother's knowledge of nutrition and feeding patterns of events less nutrition on a toddler so it can do the efforts of health promotion to lower numbers of less nutrients swoop on toddlers. This research method is quantitative analytic and use case control design. Sample of this research is getting by total sampling methods for case group as much as 50 toddler with nutrition deficiency. And use purposive sampling for control group as much as 50 toddler with good nutrition. Data collected by using questionnaires and analized by using Chi Square test. The Chi Square test results for mother's knowledge about nutrition gained 2hitung value 6.978 (p-value = 0.031) and the Odd ratio (OR) value 2.9. As for the feeding pattern gained 2hitung value 41.558 (p-value = 0.000) and the Odd ratio (OR) value 6.3. Conclusion of this study is there is the influence of the mother's knowledge of nutrition and feeding patterns on events nutrition deficiency on toddler where mothers with less knowledge are at risk of having children with nutrition deficiency as 2.9 times than mothers with good knowledge and toddler with less feeding patterns have risk of 6.3 times suffered nutrition deficiency than toddler with good feeding pattern.